Emerging Concepts in Nutrient Needs. (1st October 2020) - Stover, Patrick J; Garza, Cutberto; Durga, Jane; Field, Martha S
ABSTRACT: Dietary reference intakes (DRIs) are quantitative, nutrient intake–based standards used for assessing the diets and specific nutrient intakes of healthy individuals and populations and for informing national nutrition policy and nutrition programs. Because nutrition needs vary by age, sex, and physiological state, DRIs are often specified for healthy subgroups within a population. Diet is known to be the leading modifiable risk factor for chronic disease, and the prevalence of chronic disease is growing in all populations globally and across all subgroups, but especially in older adults. It is known that nutrient needs can change in some chronic disease and other clinical states. Disease states and/or disease treatment can cause whole-body or tissue-specific nutrient depletion or excess, resulting in the need for altered nutrient intakes. In other cases, disease-related biochemical dysfunction can result in a requirement for a nonessential nutrient, rendering it as conditionally essential, or result in toxicity for a food component at levels usually tolerated by healthy people, as seen in inborn errors of metabolism. Here we summarize examples from a growing body of literature of disease-altering nutrient requirements, supporting the need to give more consideration to special nutrient requirements in disease states.